Role of Protein Phosphorylation and Tyrosine Phosphatases in the Adrenal Regulation of Steroid Synthesis and Mitochondrial Function - Paz, Cristina; Cornejo Maciel, Fabiana; Gorostizaga, Alejandra; Castillo, Ana F.; Mori Sequeiros García, M. Mercedes; Maloberti, Paula M.; Orlando, Ulises D.; Mele, Pablo G.; Poderoso, Cecilia; Podesta, Ernesto J. (Frontiers in Endocrinology, 2016)
In adrenocortical cells, adrenocorticotropin (ACTH) promotes the activation of several protein kinases. The action of these kinases is linked to steroid production, mainly through steroidogenic acute regulatory protein (StAR), whose expression and activity are dependent on protein phosphorylation events at genomic and non-genomic levels. Hormone-dependent mitochondrial dynamics and cell proliferation are functions also associated with protein kinases. On the other hand, protein tyrosine dephosphorylation is an additional component of the ACTH signaling pathway which involves the “classical” protein tyrosine phosphatases (PTPs), such as SHP2 (src homology domain (SH) 2 containing PTP), and members of the MAP kinase phosphatase (MKP) family, such as MKP-1. PTPs are rapidly activated by post-translational mechanisms and participate in hormone-stimulated steroid production. In this process, the SHP2 tyrosine phosphatase plays a crucial role in a mechanism that includes an acyl-CoA synthetase-4 (Acsl4), arachidonic acid (AA) release and StAR induction. In contrast, MKPs in steroidogenic cells have a role in the turn-off of the hormonal signal in ERK-dependent processes such as steroid synthesis and, perhaps, cell proliferation. This review analyzes the participation of these tyrosine phosphates in the ACTH signaling pathway and the action of kinases and phosphatases in the regulation of mitochondrial dynamics and steroid production. In addition, the participation of kinases and phosphatases in the signal cascade triggered by different stimuli in other steroidogenic tissues is also compared to adrenocortical cell/ACTH and discussed.